The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/molbev/msx194
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Selection Response due to Polygenic Adaptation from a Multilocus, Multiallelic Genetic Architecture

Abstract: The ability of a population to adapt to changes in their living conditions, whether in nature or captivity, often depends on polymorphisms in multiple genes across the genome. In-depth studies of such polygenic adaptations are difficult in natural populations, but can be approached using the resources provided by artificial selection experiments. Here, we dissect the genetic mechanisms involved in long-term selection responses of the Virginia chicken lines, populations that after 40 generations of divergent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 68 publications
7
54
0
Order By: Relevance
“…An analysis of QTLs for commercially valuable traits in farm animals supports well the conclusion that recessive variation maintained in a population plays an important role [73][74][75]. The majority of the traits are related to morphological and physiological characteristics affected by stabilizing selection.…”
Section: Discussionsupporting
confidence: 56%
“…An analysis of QTLs for commercially valuable traits in farm animals supports well the conclusion that recessive variation maintained in a population plays an important role [73][74][75]. The majority of the traits are related to morphological and physiological characteristics affected by stabilizing selection.…”
Section: Discussionsupporting
confidence: 56%
“…Modeling of ample experimental data has shown that well reproducible results are obtained with both of the models, none of them is possible to prefer over the other (Zhang, Hill, 2005). An analysis of QTLs for commercially valuable traits in farm animals supports well the conclusion that recessive variation maintained in a population plays an important role (Andersson, Georges, 2004;Hill, 2014;Zan et al, 2017). The majority of the traits are related to morphological and physiological characteristics affected by stabilizing selection.…”
Section: Discussionsupporting
confidence: 56%
“…We have earlier developed a multi locus approach to explore the genetic architecture of 326 highly polygenic traits and a detailed description of the approach is available in (Sheng et al 327 2015;Brandt et al 2017;Lillie et al 2017). In short, the method was designed to study traits 328 where earlier data suggest them to be polygenic in the analysed population.…”
Section: Multi-locus Backward Elimination Association Analysis 325mentioning
confidence: 99%
“…The additional burden of corrections also for 57 population structure decreases power further. By making combined use of powerful model 58 populations, and new analytical approaches accounting for the polygenic nature of complex 59 adaptive traits, it is possible to dissect polygenic genetic architecture with greater sensitivity 60 in order to facilitate deeper insights to the genetic basis of adaptive traits (Sheng,Pettersson,61 Honaker, Siegel, & Carlborg, 2015; Zan et al, 2017). These potent statistical methods have 62 so far not been adapted to analyses of natural populations, but could be useful also for 63 identifying the genetic mechanisms that govern adaptation for polygenic traits in nature.…”
Section: Introductionmentioning
confidence: 99%